Communicating biodiversity conservation to secondary school students through a university-based botanic garden - Malabayabas, Felisa L. (The Philippine Journal of Development Communication, 2009)
This study contributes to development communication literature on environmental education communication. It investigated the effectiveness of a university-based botanic garden, the Makiling Botanic Gardens (MBG), in communicating biodiversity conservation to its visitors, particularly high school students. The students toured the MBG and watched a short film on forests. The study sought to: 1) find out the differences in the respondents' knowledge of and attitude towards biodiversity conservation before and after their visit to MBG; and 2) determine if there exists a relationship between the knowledge and attitude of respondents after their visit to MBG.